Elaboración de una guía didáctica de actividades para la recuperación pedagógica en niños de quinto año de educación general básica en el área de lengua y literatura - Torres Cordero, Camila Genoveva (2015)
This thesis deals with the issue of the elaboration of a Teaching Didactic Guide of Activities for Educational teaching Recovery in children's fifth year of basic general education in the area of Language and Literature, which was made a research about several theories concerning the child's development from birth to entry into adolescence, emphasiszing on the age of nine to ten years. The research work presents about theorists such as Piaget, Vygotsky, Ausubel, among others, who will present his theorical contributions on the child development. Secondly it makes mention about Language and Literature, it can be seen from the curriculum, where it talks about skills that the child must be acquire throughout the year and the area. Thirdly, it presents an investigation of what is a pedagogical recovery viewed from constructivism, in terms of the student as an active subject and the teacher as a facilitator of knowledge. In addition it gives an explanation of what comes to be the pedagogical recovery, as well as their importance inside the school. Finally, provides an explanation of the teaching guide in the area of Language and Literature, provides a guideline for their use in the educational institution and the teacher, always with the support of the curriculum, in order to strengthen those skills that requires the student to improve their learning process.